2006
DOI: 10.1007/s00330-006-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the uterus and cervix in healthy women: Determination of normal values

Abstract: The purpose of this study was to establish normal values for the volume of the uterus and cervix in MRI based on age and the menstrual cycle phase. We performed MRI of the pelvis in 100 healthy women. For the uterus, they were further divided into two groups: one with myomas and/or adenomyosis and one without either. The volume of the uterus and cervix and thickness of the uterine wall layers were analysed by age and the menstrual cycle phase. The mean volume of the uterus in both groups and the cervix signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 24 publications
5
58
1
1
Order By: Relevance
“…The reported increased nuclear area in the IM [12], different water content [21], and distribution of laminin β 2 [13] suggest that local anatomical differences may account for the zonation seen on MRI. MRI features suggestive of adenomyosis are indirect and include increased JZ thickness [6,20,22]. We demonstrated that the IM of normal uteri has higher cell density and total nuclear area compared to the OM (1.6- to 1.8-fold), but importantly that the change in cell density is gradual throughout the uterine thickness.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The reported increased nuclear area in the IM [12], different water content [21], and distribution of laminin β 2 [13] suggest that local anatomical differences may account for the zonation seen on MRI. MRI features suggestive of adenomyosis are indirect and include increased JZ thickness [6,20,22]. We demonstrated that the IM of normal uteri has higher cell density and total nuclear area compared to the OM (1.6- to 1.8-fold), but importantly that the change in cell density is gradual throughout the uterine thickness.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that the in vivo difference in cell density between the IM and OM may in fact be larger than the differences noted in formalin-fixed tissue. It is possible that the subendometrial halo seen on MRI reflects a transitional point of cell count or water content, but it remains unclear why this zone is not seen in all uteri [22]. On the other hand, the finding of similar expression of the intracellular components α-SMA and desmin supports reduced extracellular fluid content in adenomyosis, thus the reason for increased JZ thickness in affected uteri remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The JZ thickness increases with age between 20 and 50 years. 12 Kunz et al 8 reported a gradual increase in diameter of the posterior JZ myometrium starting in the third decade of life, which is accelerated markedly in women >34 years old and found that the posterior JZ thickness was invariably higher in patients with endometriosis, yet the agedependent increase paralleled that of women without endometriosis.…”
mentioning
confidence: 99%
“…The appearance and size of the uterine layers change in response to a variety of physiologic effects depending on the postmenopausal status (Kido et al, 2003;Hauth et al). Our results show that there is a significant decrease in the volume of uterine layers in the postmenopausal women according to three methods, except the endometrium volume where ellipsoid method was used.…”
Section: Discussionmentioning
confidence: 73%
“…In these images, the endometrium appears a high signal intensity zone, while the outer myometrium appears a medium intensity zone. The Junctional zone appears low signal intensity zone and separates the endometrium from the outer myometrium (Hauth et al, 2007;Wasnik et al, 2011;He et al, 2016).…”
Section: Introductionmentioning
confidence: 99%